2021
DOI: 10.37992/2021.1201.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in linseed germplasm using morphological traits

Abstract: The genetic diversity among 61 linseed genotypes along with 4 checks was studied in the present investigation at the Experimental Farm of Punjab Agricultural University, Regional Research Station, Gurdaspur. Results revealed that the sufficient genetic variability was observed for all the characters studied based on various genetic variability parameters. High heritability coupled with high genetic advance for plant height, technical height, capsules per plant, test seed weight and seed yield per plant indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…and Fig3) Kumar and Kumar (2021). in their Principal Component Analysis (PCA) study in linseed germplasm indicated that, five PCs contributed 84.68 per cent to the total variance amongst the genotypes assessed for agronomic traits which indicated the presence of genetic diversity and https://doi.org/10.37992/2021.1202.075Alarmelu et al, …”
mentioning
confidence: 96%
“…and Fig3) Kumar and Kumar (2021). in their Principal Component Analysis (PCA) study in linseed germplasm indicated that, five PCs contributed 84.68 per cent to the total variance amongst the genotypes assessed for agronomic traits which indicated the presence of genetic diversity and https://doi.org/10.37992/2021.1202.075Alarmelu et al, …”
mentioning
confidence: 96%